Curvilinear balconies, Fairlawn - Ghosh, Ayan (Jio Institute, 2023)
Curvilinear balconies on both sides of the central stairway, Fairlawn. The balconies have a wavy band running along the bottom edge. This contouring element was typical of the Art Deco period and appears in several buildings along Maharshi Karve Marg, usually used on balconies and above the entrance porch.